DNA methylation and sexual dimorphism: New insights from mealybugs. Issue 22 (5th November 2021) - Sarkies, Peter
Abstract : DNA methylation is an ancient epigenetic pathway found across eukaryotes. Nevertheless, the targets of DNA methylation within genomes evolve extremely rapidly. Arthropods display many such examples. The mealybug Planococcus citri has evolved methylation at promoter sequences, associated with gene silencing just as in mammals. In this issue of Molecular Ecology, Bain et al. (2021), thoroughly characterise mealybug methylation, exploring its potential functions in gene expression and the spectacular sexual dimorphism that is a characteristic of this species. Their results provide new insights into the complex relationship between DNA methylation and gene expression and highlight how rapidly different methylation systems can evolve.